VALIDITAS HADIS TIDAK ADA KISAS BAGI ORANG TUA YANG MEMBUNUH ANAKNYA - Moh. Ahsanuddin Jauhari; Enceng Arif Faizal; Syahrul Anwar; Atep Mastur; Deden Najmudin (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: One of mawâniʿ al-qishâsh is that victims are part of the perpetrators. That is, parents who kill their children can not be sanctioned qishâsh. This is based on the hadith of the Prophet which states that,